Real-Time Neuropsychological Testing Protocol for Left Temporal Brain Tumor Surgery: A Technical Note and Case Report - Tomasino, Barbara; Guarracino, Ilaria; Ius, Tamara; Maieron, Marta; Skrap, Miran (Frontiers in Human Neuroscience, 2021)
Background: The risk of surgery in eloquent areas is related to neuropsychological dysfunctions. Maximizing extent of resection increases overall survival. The onco-functional balance is mandatory when surgery involves cognitive areas: maximal information on the patients’ cognitive status during awake surgery is needed. This can be achieved by using direct cortical stimulation mapping and, in addition to this, a neuropsychological monitoring technique called Real-Time Neuropsychological testing (RTNT). RTNT includes testing protocols according to the area where surgery is performed. We report on tests used for left temporal lobe surgery and our RTNT decision tree. Case Report: We report our RTNT experience with a 25-year old, right-handed man with 13 years of schooling. He reported daily partial seizures. MRI revealed the presence of a low-grade glioma involving the temporo-insular cortex. The neuropsychological status pre-surgery which was within the normal range was combined with fMRI and DTI information. Awake surgery plus RTNT was performed. Direct Electrical Stimulation (DES) during object naming elicited a motor speech arrest. Resection was continuously accompanied by RTNT. RTNT provided enriched information to the surgeon. Performance never dropped. A slight decrement in accuracy emerged for pseudoword repetition, short-term memory and working memory, for phonological processing and verbal comprehension. Total resection was performed, and the histological examination confirmed the nature of the lesion. Immediate post-surgery performance was within the normal range as it was the fMRI and DTI assessment. Conclusion: The RTNT provides essential information that can be used online, during surgery, for clinical aims to provide the surgeon with useful feedback on the patient’s cognitive status.